Konstruksi Identitas Virtual Melalui Media Sosial: Kajian Dramaturgi pada Akun Facebook Rima Susanti - Yayu R. Mayangsari; Firdaus Firdaus; Rahmi Rahmi (Lembaga Pengembangan Kinerja Dosen, 2026)
Social media has now changed the way individuals construct, display, and manage their identities in public spaces. Rima Susanti's professional Facebook account is interesting to study using Ervin Goffman's dramaturgical theory because it represents a person's identity in the digital world. The purpose of this study is to determine how dramaturgy works behind the management of Rima Susanti's professional Facebook account. This study uses a descriptive qualitative approach. The study was conducted by observing the contents of